HAMBATAN-HAMBATAN YANG DIALAMI TUTOR DALAM PEMBELAJARAN PAKET B SETARA SLTP DI SANGGAR KEGIATAN BELAJAR (SKB) LUBUK BEGALUNG KOTA PADANG - Nova Devista (JIV-Jurnal Ilmiah Visi, 2007)
Tutors play a very important role in instructional process in B Package Program equivalent to Junior Secondary School as they have to face learners and to plan, organize, and evaluate the instructional process. This research intended to discover obstacles faced by the tutors of B Package Program in Lubuk Begalung in completing their task. This research employed qualitative approach and the data were collected by using observation technique, interview, and document study. The informers were tutors and program executers. The data were analyzed using the method recommended by Miles and Huberman (1992) which was consisted of reducing the data, presenting the data, and drawing the conclusion. The finding of this research shows a set of obstacles faced by the tutors. Beside the efforts have been taken to overcome the obstacles, it is recommended to provide trainings for the tutors and program executors in order to read improve the implementation and the attainment of the obstacles of the program.